GAYA DAN ELEMEN VISUAL ARSITEKTUR BANGUNAN KOLONIAL GEDUNG KARESIDENAN BAKORWIL III PURWOKERTO ATAU HETERO SPACE, PURWOKERTO - Artanti Kusuma Ayu; Revi Aulia Purbandini; Eva Priyanti (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
The relocation of the administrative city from Banyumas to Purwokerto in 1937 was one of the key moments in the history of colonial governance in Central Java. The Bakorwil III Residency Building in Purwokerto, which is now (2025) Hetero Space, was constructed as a government center to support administrative functions in the region. This building not only became a symbol of colonial power but also reflected the social and economic changes of that era. This research aims to analyze the architectural style and visual architectural elements of the colonial buildings within the Bakorwil Residency Building in Purwokerto. The method used is descriptive qualitative. Data collection was conducted through observation, literature review, and interviews. The research findings show that the architectural style of the Bakorwil Residency Building in Purwokerto was influenced by modern colonial architecture (1915-1940) and the Art Deco style.